Hubungan Motivasi Kerja Dengan Kinerja Karyawan Administrasi Di Rumah Sakit Umum Daerah Tugu Koja Tahun 2023 - Atikah Fitria Ningsih; Ria Efkelin; Lipin Lipin; Martini Martini; Ary Rahmaningsih; Imelda Imelda; Hingawati Setio (Lembaga Pengembangan Kinerja Dosen, 2023)
Motivation is the driving force for a person or individual to carry out activities toward obtaining the desired thing, both positively and negatively. With this motivation, an effort is made to encourage employees to be more active at work to achieve maximum service to the community. Performance is how employees show their work performance through concrete actions. Employee performance is influenced by internal and external factors. Internal factors include work motivation, personality, attitudes, and behavior. While external factors include superior leadership style, employee relations, and the work environment, The purpose of this study aimed to examine the relationship between work motivation and the performance of administrative employees at Tugu Koja Hospital. The method in this study used a quantitative method with a descriptive approach, and the test used was Spearman's rho. This res earch was conducted at Tugu Koja General Hospital in the administrative section with a total of 37 respondents. The results obtained after the Spearman rho test were 0.861, with a significant value of 0.000. Based on the test results, it was concluded that there is a strong relationship between the performance of health administration employees and it can be concluded that there is a significant relationship between work motivation and employee performance at Tugu Koja Hospital.